المثقف وصراع الأيديولوجيات في رواية الغربان لحسين الواد (مجلة إحالات, 2025)
الملخص: جاء مقالنا ليبحث عن دور المثقف فيما يسمى بثورات الربيع العربي، حيث سنقوم بعملية مسح لأنواع المثقفين في رواية الغربان حتى نصل إلى " المثقف الصامت" كما صوره " حسين الواد" في الرواية؛ باعتباره مثقفا محايدا يعيش على هامش المجتمع نتيجة ضربات عدة أخَّلت بدوره المعهود في المجتمعات التي تعرف ثورات اجتماعية أو سياسية يكون المثقف فيها هو المرشد والمبلور للفكر الجماهيري وهذا ما غاب عن المثقف العربي – التونسي- الذي اكتفى بمراقبة الصراع الإيديولوجي داخل المجتمع دون أن يبدي أي رأي، وهذا ما حاول "الواد" أن يعالجه في روايته "الغربان".summary: Our article came to search for the role of the intellectual in the so-called Arab Spring revolutions, where we will conduct a survey of the types of intellectuals in the novel Crows until we reach the "silent intellectual" as depicted by "Hussein Al-Wad" in the novel, as a neutral intellectual who lives on the margins of society as a result of several strikes that disrupted the usual In societies where social or political revolutions are known, the educated person is the guiding and crystallizing of the mass thought, and this is what was absent from the Arab-Tunisian intellectual who was content with observing the ideological struggle inside society without expressing any opinion, and this is what the "father" tried to address in his novel "Crows" ".